Coronary Artery Calcium Progression and Atrial Fibrillation: The Multi-Ethnic Study of Atherosclerosis. (December 2015) - O'Neal, Wesley T.; Efird, Jimmy T.; Qureshi, Waqas T.; Yeboah, Joseph; Alonso, Alvaro; Heckbert, Susan R.; Nazarian, Saman; Soliman, Elsayed Z.
Abstract : Background—: Coronary artery calcium (CAC) measured at a single time point has been associated with an increased risk for atrial fibrillation (AF). It is unknown whether CAC progression over time carries a similar risk. Methods and Results—: This analysis included 5612 participants (mean age: 62±10; 52% women; 39% whites; 27% blacks; 20% Hispanics; 12% Chinese Americans) from the Multi-Ethnic Study of Atherosclerosis. Phantom-adjusted Agatston scores for baseline and follow-up measurements were used to compute change in CAC per year (⩽0, 1–100, 101–300, and >300 U/year). AF was ascertained by review of hospital discharge records and from Medicare claims data through December 31, 2010. Cox regression was used to compute hazard ratios (HR) and 95% confidence intervals (CI) for the association between CAC progression and AF. Over a median follow-up of 5.6 years (25th, 75th percentiles=5.1, 6.8), a total of 203 (3.6%) incident AF cases were detected. Any CAC progression (>0/year) was associated with an increased risk for AF (HR=1.55, 95% CI=1.10, 2.19), and the risk increased with higher levels of CAC progression (⩽0/year: HR=1.0 [reference]; 1–100/year: HR=1.47, 95% CI=1.03, 2.09; 101–300/year: HR=1.92, 95%CI=1.15, 3.20; >300/year: HR=3.23, 95%CI=1.48, 7.05). An interaction was observed by age with the association of CAC progression with AF being stronger for younger (<61 years: HR=3.53, 95% CI=1.29, 9.69) compared with older (≥61 years: HR=1.42, 95% CI=0.99, 2.04) participants ( P interaction=0.037). Conclusions—: CAC progression during an average of 5 to 6 years of follow-up is associated with an increased risk for AF.